ANALISIS KESEDIAAN MEMBAYAR BIAYA PENGELOLAAN SAMPAH, STUDI KASUS PADA PENGHUNI KOMPLEK PERUMAHAN BTN PAGESANGAN INDAH - Cita, Fitriah Permata; Suwardi, Didi; Vinuzia, Mala (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study aims to analyze the factors influencing residents’ willingness to pay (WTP) and the amount they are willing to pay for solid waste management services in the BTN Pagesangan Indah Housing Complex, Mataram City. The research employs a quantitative descriptive approach using a survey method. A total of 60 household heads were selected through simple random sampling from a population of 178 households. Logistic regression analysis was applied to examine the factors affecting willingness to pay, while multiple linear regression was used to analyze the determinants of the amount of willingness to pay. The independent variables include household income, education level, number of household members, membership in environmental organizations, amount of waste generated, and perception of environmental quality. The results indicate that all independent variables simultaneously have a significant effect on residents’ willingness to pay for waste management services. Partially, household income and education level significantly influence the amount of willingness to pay. The coefficient of determination shows that the model explains 43.8 percent of the variation in the amount of willingness to pay, while the remaining variation is influenced by other factors outside the model. These findings are expected to provide useful insights for policymakers in designing community-based waste management policies in urban residential areas.